Does economic growth moderate the effect of fundamental values on the stock return of Indonesian infrastructure companies? - Dody Hapsoro; Al-iefan Kharismawan Syahriar (Universitas Hayam Wuruk Perbanas, 2021)
In recent years, issues of infrastructure development and economic growth have become very popular topics during President Jokowi’s administration. Infrastructure development is expected to have an impact on economic growth. The purpose of this study was to examine the effect of fundamental values on the stock returns of infrastructure companies listed on the Indonesia Stock Exchange in 2015-2017 with economic growth as a moderating variable. This research uses a purposive sampling technique. The analytical method used is partial least squares with WarpPLS software version 6.0. the results show that EPS has a positive effect on stock returns while DER, PER, and NPM do not affect stock returns. Furthermore, it also indicates that economic growth does not moderate the effect of EPS and DER on stock returns. However, the results of the study prove that economic growth can moderate the effect of PER and NPM on stock returns. This research implies that government policy that sets priorities for infrastructure development needs to be supported because it is proven that the government policy has a positive effect on the profits and stock returns of infrastructure companies.